Sparse-regular aperture array SKA telescope concept - De Vaate, J.; Davidson, David; Razavi-Ghods, N. (2017)
© 2018 Electromagnetics Academy. All rights reserved. Sparse-regular phased- or aperture arrays are generally disregarded due to the presence of grating lobes. However for receive only systems consisting of multiple stations, good system performance can be achieved by station rotation, enabling cost effective solutions with overall good performance.